Digital Transformation in Arabic Language Learning: Utilizing Learning.Al-Jazeera.Net To Enhance Listening Comprehension (Maharah Istima’) - Baity, Anggi; Khoirunnisa, Alifia; Ridha ‘Atiqotul Hamidah (Universitas Islam Tribakti Lirboyo, Kediri, 2024)
This study focuses on the challenges of enhancing Arabic listening skills (maharah istima’) in the digital era and the importance of utilizing authentic media for effective learning. Learning Al-Jazeera.Net was chosen as it provides access to relevant and contextual Arabic audio resources. The study aims to evaluate the effectiveness of using Learning Al-Jazeera.Net in developing students’ listening skills at IAIN Kediri. A qualitative research approach was used, involving observation and descriptive analysis, with a structured implementation of this media. This includes audio listening exercises, pronunciation imitation, and contextual comprehension practice. The findings indicate that Learning Al-Jazeera.Net is effective in enriching students' learning experiences, facilitating the acquisition of new vocabulary, and improving pronunciation accuracy and sensitivity to dialect variations. However, challenges were identified regarding the stability of question features on mobile devices, limiting learning flexibility. Overall, this media supports listening skill development and provides a more contextual and realistic Arabic learning experience for students.